Regional cerebrovascular oxygen saturation measured by optical spectroscopy in humans - McCormick, P W; Stewart, M; Goetting, M G; Balakrishnan, G (Stroke (1970), 1991)
Regional cerebrovascular oxygen saturation, a quantitative measure of hemoglobin saturation in the combined arterial, venous, and microcirculatory compartments of the brain, can be measured noninvasively with near infrared spectroscopy. We assessed the sensitivity of this aggregate saturation to cerebral hypoxia during transient cerebral hypoxic hypoxia in seven human subjects. Regional cerebrovascular oxygen saturation measured over the middle frontal gyrus and analog electroencephalogram were recorded. We compared the time to achieve two end points: the earliest paroxysmal burst of theta-delta background slowing and a cerebrovascular oxygen saturation of less than 55%. Saturation fell below 55% prior to the electroencephalographic change (p less than 0.05). In a related effort, we also compared spectroscopically measured regional cerebrovascular oxygen saturation with an estimate of this value calculated from arterial and cerebral mixed venous saturation in nine patients. A positive linear relation (n = 68, R2 = 0.55, s = 4.2) was noted.